An inertial macroelement for bridge abutments. Issue 3 (6th November 2020) - Gorini, Davide Noè; Callisto, Luigi; Whittle, Andrew J.
Abstract : In recent years, the designers of long girder bridges in seismic areas have frequently opted for a continuous deck. One implication of this choice is that in many instances bridge abutments are called upon to carry large seismic forces, engaging the dynamic response of the soil–abutment system. To deal with this problem, this paper describes the formulation of a novel one-dimensional, inertial macroelement for simulating the dynamic behaviour of bridge abutments. The non-linear force–displacement relationship is characterised by a multi-surface plasticity model using a rigorous thermodynamic approach. The plastic response of the model is bounded by the ultimate capacity of the soil–abutment system that includes dissymmetry of the soil response in active and passive loading directions, while inertial effects transferred by the near-field approach embankment are simulated through appropriate participating masses in the macroelement formulation. The paper describes a straightforward calibration procedure of the proposed macroelement for horizontal, longitudinal loading of the abutment. The macroelement has been incorporated into a simplified, global, finite-element model of a multi-span girder bridge and validated through comparisons with results from a full three-dimensional (3D) dynamic time domain analysis under seismic loading. The inertial macroelement predictions of abutment deformations, axial deck loads and pier reaction forces are in very good agreement with the 3D soil–structure interaction model, and are achieved at much lower computational costs. The proposed inertial macroelement represents a significant improvement over existing simplified models based on linear response of the soil–abutment system.